The macroeconomic consequences of import tariffs and trade policy uncertainty - Lukas Boer; Malte Rieth (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
We estimate the macroeconomic effects of import tariffs and trade policy uncertainty in the United States, combining theory-consistent and narrative sign restrictions on Bayesian SVARs. We find mostly adverse consequences of protectionism. Tariff shocks are more important than trade policy uncertainty shocks. Tariff shocks depress trade, investment, and output persistently, in aggregate and across sectors and space. The general equilibrium import elasticity is -0.8. Historically, NAFTA/WTO raised output by 1-3% for twenty years. Undoing the 2018/19 measures would raise output by cumulatively 4%. The findings imply higher output costs of protectionism than partial equilibrium or static trade models.
Keywords: C32; E30; F13; F14; 330; Trade policy; international trade; structural vector autoregressions; narrative identification; general equilibrium; United States